Is quality and availability of facilities at Primary Health Centers (PHCs) associated with healthcare-seeking from PHCs in rural India: An exploratory cross-sectional analysis - Akif Mustafa; Chander Shekhar (Elsevier, 2021)
Objective: The present study aims to analyze the association between the availability of facilities at PHCs and their association with healthcare-seeking from PHCs in rural India. Data and methods: The data used in the study were extracted from HMIS (Health Management Information System) and NFHS-4. Using 'HMIS rural health infrastructure data' we constructed the 'Facility Index' at the district level by performing Exploratory Factor Analysis. Multilevel logistic regression and concentration curve were employed to analyze the association between the availability of facilities at PHCs (Facility Index) and healthcare-seeking from PHCs. Results: Facility Index was found to be positively associated with healthcare-seeking from PHCs. The results of multilevel regression analysis showed that people from districts with 'very good' facility index were four times (AOR: 4.01, CI: 3.54-4.52) more likely to visit PHC compared to districts with 'very poor' facility index while controlling the effect of background variables. The concentration curve showed that in the districts with higher facility index people were more prone to seek healthcare from PHC compared to districts with lower facility index (Concentration Index: 0.175, standard error: 0.0026). Conclusion: Based on our findings we can expect that if the government improves the quality and availability of facilities at PHCs then it is more likely that people will choose PHCs for general healthcare-seeking. We believe that the findings of the present study have important policy implications.